2015
DOI: 10.3935/ljsr.v22i1.83
|View full text |Cite
|
Sign up to set email alerts
|

Restorative Justice and Recidivism: Investigating the Impact of Victim-Preference for Level of Engagement

Abstract: The aim of this study was to assess the impact of offering victims choice in their level of engagement with restorative justice interventions. Consequently, this study compared the expected risk for reconviction, calculated using the Offender Group Reconviction Scale and actual reconviction rates for completers and non-completers of three different restorative justice (RJ) initiatives: conference, letter of apology and victim-empathy work. Where reconvictions were evident the comparative level of harm between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…In contrast to the findings, however, recent research concluded that letters of apology were significantly effective for both property and low-level offences (Wager et al , 2015). In addition, an imbalance in the verbal skills required for direct communication has been reported within the literature, often due to the culture, ethnicity or socioeconomic background of the individuals (Willis, 2020; Willis and Hoyle, 2019).…”
Section: Findings and Discussioncontrasting
confidence: 76%
“…In contrast to the findings, however, recent research concluded that letters of apology were significantly effective for both property and low-level offences (Wager et al , 2015). In addition, an imbalance in the verbal skills required for direct communication has been reported within the literature, often due to the culture, ethnicity or socioeconomic background of the individuals (Willis, 2020; Willis and Hoyle, 2019).…”
Section: Findings and Discussioncontrasting
confidence: 76%
“…Restorative justice models can involve formal and informal procedures meant to give voice to the victim and encourage reflection and rehabilitation for the offender (Hopkins, 2012; Ptacek & Frederick, 2008). While processes used to achieve these goals can vary substantially, all restorative processes share a commitment to identifying and articulating the impact of harms and finding responses that ameliorate those harms (Goodmark, 2015; Koss et al, 2004; Wager et al, 2015); restorative justice can be embedded within systems. By contrast, the transformative justice model positions restorative principles outside the justice system, to hold communities accountable for their role in violence and transform the conditions that facilitate abuse (Coker, 2002).…”
Section: Introductionmentioning
confidence: 99%